Energy maximization of Old PV array under discoloration conditions using different interconnection schemes - Al Mansur, Ahmed; Alam, Sabbir; Leyon, Shaquar Islam; Tohid, Sabbir Hasan; Ahmmed, Kamran; Alom, Shahin; Haider, Chowdhury Shajjad; Rahman, Mostafizur; Islam, Imamul; Ustun, Taha Selim (Institute of Electrical and Electronics Engineers Inc., 2023)
Discoloration of solar panels is a phenomenon where the color of the panels changes over time due to numerous environmental variables such as temperature, irradiance, and humidity. Discoloration causes a significant impact on the PV performance reduction considering output power. The power degradation increases gradually due to the increment of discoloration of aged PV array modules. In this work, the effect of discoloration has been investigated practically by considering a five-year aged 200 W PV array. The array modules are connected in 4×5 array configurations and the power rating of each module is 10W. The PV modules are tested individually using a professional PV tester and visual imaged-based investigations have been made to identify the discoloration effects on each module output power. Based on these results the array modules are rearranged to increase the output power using a module rearranged technique. Moreover, five different interconnection schemes are applied to make a comparative investigation considering the PV array output power and percentage of recoverable energy. The experimental results show that the BL interconnection scheme can generate 4.93% more energy than the typical SP interconnection.